Comparative Study of CFRP-Confined CFST Stub Columns under Axial Compression - Ying Guo; Yufen Zhang (Advances in Civil Engineering)
This paper presented a comparative study of concrete-filled steel tubular (CFST) stub columns with three different confinement types from carbon fiber reinforced polymer (CFRP): outer circular CFRP, inner circular CFRP, and outer square CFRP. The compressive mechanism and physical properties of the composite column were analyzed firstly aiming at investigating the confinement effect of CFRP. Ultimate axial bearing capacity of these three CFRP-confined CFST columns was calculated based on Unified Theory of CFST and elastoplastic limit equilibrium theory, respectively. Meanwhile, the corresponding tests are adopted to validate the feasibility of the two calculation models. Through data analysis, the study confirmed the ultimate strength calculation results of the limit equilibrium method were found to be more reliable and approximate to the test results than those of Unified Theory of CFST. Then axial bearing capacity of the pure CFST column was predicted to evaluate the bearing capacity enhancement ratio of the three types of composite columns. It was demonstrated that the averaged enhancement ratio is 16.4 percent, showing that CFRP-confined CFST columns had a broad engineering applicability. Through a comparative analysis, this study also confirmed that outer circular CFRP had the best confinement effect and outer square CFRP did better than inner circular CFRP. The confinement effect of CFRP increased with the decrease of concrete strength, and it was proportional with relative proportions of CFRP and steel under the same concrete strength.